Associations of Multimorbidity with Cerebrospinal Fluid Biomarkers for Neurodegenerative Disorders in Early Parkinson's Disease: A Cross-sectional and Longitudinal Study - Zhang, Ming-Zhan; Sun, Yan; Chen, Yan-Ming; Guo, Fan; Gao, Pei-Yang; Tan, Lan; Tan, Meng-Shan (Current Alzheimer Research, 2024)
ObjectThe study aims to determine whether multimorbidity status is associated with cerebrospinal fluid (CSF) biomarkers for neurodegenerative disorders.MethodsA total of 827 patients were enrolled from the Parkinson’s Progression Markers Initiative (PPMI) database, including 638 patients with early-stage Parkinson’s disease (PD) and 189 healthy controls (HCs). Multimorbidity status was evaluated based on the count of long-term conditions (LTCs) and the multimorbidity pattern. Using linear regression models, cross-sectional and longitudinal analyses were conducted to assess the associations of multimorbidity status with CSF biomarkers for neurodegenerative disorders, including α-synuclein (αSyn), amyloid-β42 (Aβ42), total tau (t-tau), phosphorylated tau (p-tau), glial fibrillary acidic protein (GFAP), and neurofilament light chain protein (NfL).ResultsAt baseline, the CSF t-tau (p = 0.010), p-tau (p = 0.034), and NfL (p = 0.049) levels showed significant differences across the three categories of LTC counts. In the longitudinal analysis, the presence of LTCs was associated with lower Aβ42 (β < -0.001, p = 0.020), and higher t-tau (β = 0.007, p = 0.026), GFAP (β = 0.013, p = 0.022) and NfL (β = 0.020, p = 0.012); Participants with tumor/musculoskeletal/mental disorders showed higher CSF levels of t-tau (β = 0.016, p = 0.011) and p-tau (β = 0.032, p = 0.044) than those without multimorbidity.ConclusionMultimorbidity, especially severe multimorbidity and the pattern of mental/musculoskeletal/tumor disorders, was associated with CSF biomarkers for neurodegenerative disorders in early-stage PD patients, suggesting that multimorbidity might play a crucial role in aggravating neuronal damage in neurodegenerative diseases.
Keywords: neurofilament light chain protein